1998
DOI: 10.1590/s0066-782x1998000300004
|View full text |Cite
|
Sign up to set email alerts
|

Comparação entre a prescrição de intensidade de treinamento físico baseada na avaliação ergométrica convencional e na ergoespirométrica

Abstract: Purpose -To compare the lower (LL) and upper limits (UL) of exercise intensity prescription based on standard exercise test (60-70% of estimated VO 2 max or 70-85% of HRmax measured) with exercise intensity prescription based on cardiopulmonary exercise test [anaerobic threshold (AT) and respiratory compensation point (RCP)].Methods AT (4mph= 34.4±4.5 vs 19.6±4.6 and 5mph= 28.9±2 vs 18.9±5.4, and LPC= 32.0±4.1 vs 17.2±2.8 and MPC= 31.6±4.9 LA (4mph= 34,4±4,5 vs 19,6±4,6 e 5mph= 28,9±2 vs 18,9±5,4, e BCF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 5 publications
0
17
1
5
Order By: Relevance
“…In addition to identifying cardiovascular abnormalities 4 , the importance of performing exercise stress testing in elderly subjects before they engage in any exercise program is emphasized by these results. Together with the fact that HR based on standard exercise stress tests overestimates training intensity in young 23 and elderly subjects alike 24 when compared with exercise prescription concomitantly according to increasing exercise intensity during GXT, beginning with a mean value of 69.1 bpm (at rest) and reaching 145.5, on average, at exhaustion. This HR behavior during graded exercise is well-established in the literature, both in young and elderly subjects 15,16 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition to identifying cardiovascular abnormalities 4 , the importance of performing exercise stress testing in elderly subjects before they engage in any exercise program is emphasized by these results. Together with the fact that HR based on standard exercise stress tests overestimates training intensity in young 23 and elderly subjects alike 24 when compared with exercise prescription concomitantly according to increasing exercise intensity during GXT, beginning with a mean value of 69.1 bpm (at rest) and reaching 145.5, on average, at exhaustion. This HR behavior during graded exercise is well-established in the literature, both in young and elderly subjects 15,16 .…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, HRmax identified during GXT was closer to the traditional equation, although a significant statistical difference was found. Using the same prediction approach, earlier reports have pointed to an overestimate of HRmax measured during maximal spiroergometric tests in young 23 and elderly Brazilians 24 . In this regard, considering that the "220 -age" formula has a standard error of 10 a 12 bpm 26 and the mean difference between measured and predicted HRmax was 7.4 bpm, study patients are within the expected limits for this equation.…”
Section: Fig 1 -Relationship Between Measured Hrmax and That Estimatmentioning
confidence: 90%
“…Indirect calorimetry is a noninvasive method used for VO 2 measurement by means of an ergospirometer 5 . Difficulty of access to and high costs of ergospirometric evaluation, however, cause predictive methods to be more frequently used than ergospirometry in the assessment of functional capacity 6 . Consequently, several equations have been proposed to estimate maximal and/ or submaximal oxygen uptake based on easy-to-measure morphological and functional variables such as: body mass; age; gender; height; perceived exertion; walk time; run time; and load in watts 1,[7][8][9][10][11][12][13][14][15] .…”
mentioning
confidence: 99%
“…Conversely, further studies found opposite results, as the study by Santos (13) and Rondon et al (9) , who assessed in the conventional ergometry the O 2max estimated by regression, in which the indirect measurement overestimated the direct measurement regardless of the protocol and ergometer used. Brum et al (24) , Filardo et al (25) and Costa et al (14) assessed, respectively, the run and gait equations by the ACSM (11,26,27) for estimation of the O 2 and also found results which overestimated the direct measurement, pointing to the need to specify the study of the indirect methods by gender, age and physical status.…”
Section: Discussionmentioning
confidence: 90%
“…The direct measurement is considered gold standard for being the most reliable and it is performed through the ergospirometric test in which the individual is submitted to increasing effort loads and the oxygen expired (O 2 ) and carbon dioxide (CO 2 ) fractions are measured during exercise and pulmonary ventilation, precisely assessing hence the cardiorespiratory and metabolic capacity (8,9) . Nonetheless, the ergospirometric test presents high cost, the equipment is sophisticated and needs skilled labor to operate it, longer time for evaluation of each individual as well as higher motivation since the tests are usually performed in laboratory; these are the reasons why methods for O 2max indirect determination have been proposed (10,11) .…”
Section: Introductionmentioning
confidence: 99%